Augustine and the fundamentalist's daughter - Miles, Margaret R. (Margaret Ruth), 1937- (Cambridge : Lutterworth Press, 2012)
In Augustine and the Fundamentalist's Daughter, Margaret Miles weaves her memoirs together with reflections on Augustine's Confessions. Having read and reread Augustine's Confessions, in admiration as well as frustration, over the past thirty-five years, Miles brings her memories of childhood and youth in a fundamentalist home into conversation with Augustine's effort to understand his life. The result is a fascinating work of autobiographical and theological reflection. This project brings together a rare combination of insights on fundamentalists convictions and habits of mind. Such reflecti.
Includes bibliographical references (pages 223-227).
Print version record.
Master record variable field(s) change: 600
Keywords: Miles, Margaret R. -- 1937-; Augustine, -- of Hippo, Saint, -- 354-430 -- Criticism and interpretation; Miles, Margaret R., -- 1937-; Augustine, -- Saint, Bishop of Hippo; Miles, Margaret R. -- 1937-; RELIGION -- Christianity -- Denominations; RELIGION -- Christian Theology -- General; Electronic books; Criticism, interpretation, etc; Electronic books